The E. coli dicarboxylic acid transporters DauA act as a signal transducer by interacting with the DctA uptake system. Issue 1 (December 2017) - Karinou, Eleni; Hoskisson, Paul; Strecker, Alexander; Unden, Gottfried; Javelle, Arnaud
Abstract The Slc26A/SulP family of ions transporter is ubiquitous and widpsread in all kingdon of life. InE .coli, we have demonstrated that the Slc26 protein DauA is a C4 -dicarboxilic acids (C4 -diC) transporter active at acidic pH. The main C4 -diC transporter active at pH7 is DctA and is induced by C4 -diC via the DcuS/R two component system. DctA interacts with DcuS, the membrane embedded histidine kinase, to transfers DcuS to the responsive state, i.e. in the absence of DctA, DcuS is permanently "on", but its activity is C4 -diC-dependent when in complex with DctA. Using phenotypic characterization, transport assays and protein expression studies, we show that at pH7 full DctA production depends on the presence of DauA. A Bacterial Two Hybrid system indicates that DauA and the sensor complex DctA/DcuS physically interact at the membrane. Pull down experiments completed by co-purification study prove that DauA and DctA interact physically at the membrane. These data open a completely new aspect of the C4 -diC metabolism inE .coli and reveals how the bacterial Slc26A uptake systems participate in multiple cellular functions. This constitutes a new example of a bacterial transporter that acts as a processor in a transduction pathway.